Influence of leader sense-giving and leader promotion of team sense-making on team effectiveness: mediation role of team planning and team adaptation - Marras, Veronica (2019)
In the global, dynamic environment in which organizations are set today, the ability to adapt in response to change stimuli has become key for organizational success. Teamwork has been chosen as preferred work organization tool to ensure flexibility and adaptiveness by collecting dispersed knowledge and experience in order to manage the complexity of the work environment. Team effectiveness, as a fundamental indicator of organizational performance, has team adaptation as one of its key predictors. The ability of teams to successfully engage in adaptation processes has been showed to be influenced by another team process: team planning. Of the three types of planning classified in the literature, we focused on the transition phase deliberate and contingency planning. Leaders have been shown to have a significant influence on team processes and team outcomes. The aim of our study is to explore two leadership functions, leader sense-giving (LSG) and leader promotion of team sense-making (LPSM), as antecedents of team effectiveness, with team performance as chosen indicator. We propose and test a double mediation model with deliberate and contingency planning and team adaptation as serial mediators of the relationship between both LSG and LPSM and team effectiveness. By conducting a study on 82 consulting teams, we found support to our proposition that LSG and LPSM positively influence team performance through both team planning and team adaptation processes. Practical implications of these findings are discussed.